2010
DOI: 10.1021/ie101739q
|View full text |Cite
|
Sign up to set email alerts
|

Biosorptive Abatement of Cd2+ by Water Using Immobilized Biomass of Arthrobacter sp.: Response Surface Methodological Approach

Abstract: The present study deals with the successful utilization of bacterial biosorbent Arthrobacter sp. for the removal of Cd(II) ion from water in a batch and a continuous system. The maximum uptake capacity of free and immobilized biomass in batch system was 270.27 and 188.67 mg/g, respectively. The maximum removal percentage Cd 2+ of 88.9% was obtained at flow rate of 1.0 mL/min and 19 cm bed height in the column system. The bed depth service time (BDST) model was applied, which was found to be in good agreement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…These results showed that the immobilization procedure has no apparent effect on the surface area of the initially used free biomass. Similar results were found by Hasan and Srivastava (2010) with free and calcium alginate immobilized Arthrobacter sp. They found the BET area surfaces to be 2 and 2.3 m 2 /g, respectively.…”
Section: Surface Area Of the Cabsupporting
confidence: 88%
“…These results showed that the immobilization procedure has no apparent effect on the surface area of the initially used free biomass. Similar results were found by Hasan and Srivastava (2010) with free and calcium alginate immobilized Arthrobacter sp. They found the BET area surfaces to be 2 and 2.3 m 2 /g, respectively.…”
Section: Surface Area Of the Cabsupporting
confidence: 88%
“…It can facilitate an inspection of experimental factors in selected responses like adsorption capacity (Hasan and Srivastava 2011;Danish et al 2014b). Therefore, 3D response surface curves were plotted for a statistically significant model to explore the interaction of variables on the adsorption capacity of the produced activated carbon.…”
Section: Response Surface Plotsmentioning
confidence: 99%
“…As demonstrated in Figure 8 and Table 3, the results indicated that the breakthrough time (t b ) and the exhaustion time (t e ) of compound biosorbents were significantly delayed compared with the single biosorbents. Comparing with the data of PSH, MCH fixed bed system showed a larger q exp and shorter H. Height of mass transfer zone (H) is the reflection of mass transfer resistance of fixed bed, the shorter H means less mass transfer resistance and more utilization efficiency of fixed bed [35,36]. This result proved that combining with HA is an effective way to improve the fixed bed adsorptive capacity of biosorbent.…”
Section: Mad5mentioning
confidence: 66%